Effectiveness and cost‐effectiveness of a brief school‐based group programme for parents of children at risk of ADHD: a cluster randomised controlled trial. (July 2016) - Sayal, K.; Taylor, J. A.; Valentine, A.; Guo, B.; Sampson, C. J.; Sellman, E.; James, M.; Hollis, C.; Daley, D.
Abstract: Background: National Institute for Health and Care Excellence guidelines recommend a stepped care approach for the identification and management of children with, or at risk of, attention‐deficit/hyperactivity disorder (ADHD). We investigated the effectiveness, cost‐effectiveness and acceptability of a group parenting intervention programme (+/− a teacher session) for children at risk of ADHD. Methods: In a three‐arm cluster randomised controlled trial, 12 primary schools were randomly assigned to control, parent‐only and combined (parent + teacher) intervention arms. Eligible children had high levels of parent‐rated hyperactivity/inattention ( n = 199). At 6 month follow‐up, the primary outcome measure was the parent‐completed Conners' Rating Scale – Revised (ADHD index). Secondary outcomes included the Conners' sub‐scales (hyperactivity, cognitive problems/inattention and oppositional behaviour), the teacher‐completed Conners' Rating Scale – Revised, child health‐related quality of life, parental burden and parental mental health. The cost‐effectiveness analyses reflected a health and personal social services perspective. Trial Registration: ISRCTN87634685. Results: Follow‐up data were obtained from 76 parents and 169 teachers. There was no effect of the parent‐only (mean difference = −1.1, 95% CI −5.1, 2.9; p = 0.57) or combined interventions (mean difference = −2.1, 95% CI −6.4, 2.1; p = 0.31) on the ADHD index. The combined intervention was associated with reduced parent‐reported hyperactivity symptoms (mean difference = −5.3; 95% CI −10.5, −0.01; p = 0.05) and the parent‐only intervention with improved parental mental health (mean difference = −1.9; 95% CI −3.2, −0.5; p = 0.009). The incremental costs of the parent‐only and the combined interventions were £73 and £123, respectively. Above a willingness‐to‐pay of £31 per one‐point improvement in the ADHD index, the parent‐only programme had the highest probability of cost‐effectiveness. Participants found the interventions acceptable. Conclusions: For children at risk of ADHD, this school‐based parenting programme was not associated with improvement in core ADHD symptoms. Secondary analyses suggested a possible reduction in parent‐reported hyperactivity and parental mental health problems. Future research should compare targeted interventions against watchful waiting and specialist referral.